Screening for Cognitive Impairment After Stroke: Validation of the Chinese Version of the Quick Mild Cognitive Impairment Screen - Xu, Yangfan; Yi, Lingrong; Lin, Yangyang; Peng, Suiying; Wang, Weiming; Lin, Wujian; Chen, Peize; Zhang, Weichao; Deng, Yujie; Guo, Suimin; Shi, Le; Wang, Yuling; et al. (Frontiers in Neurology, 2021)
Background: Screening for post-stroke cognitive impairment (PSCI) is necessary because stroke increases the incidence of and accelerates premorbid cognitive decline. The Quick Mild Cognitive Impairment (Qmci) screen is a short, reliable and accurate cognitive screening instrument but is not yet validated in PSCI. We compared the diagnostic accuracy of a Chinese version of the Qmci screen (Qmci-CN) compared with the widely-used Chinese versions of the Montreal Cognitive Assessment (MoCA-CN) and Mini-Mental State Examination (MMSE-CN). Methods: We recruited 34 patients who had recovered from a stroke in rehabilitation unit clinics in two university hospitals in China: 11 with post-stroke dementia (PSD), 15 with post- stroke cognitive impairment no dementia (PSCIND), and 8 with normal cognition (NC). Classification was made based on clinician assessment supported by a neuropsychological battery, independent of the screening test scores. The Chinese versions of the Qmci-CN, MoCA-CN and MMSE-CN screens were administered randomly by a trained rater, blind to the diagnosis. Results: The mean age of the sample was 63 ±13 years and 61.8% were male. The Qmci-CN had statistically similar diagnostic accuracy in differentiating PSD from NC, an area under the curve (AUC) of 0.94 compared to 0.99 for the MoCA-CN (p=0.237) and 0.99 for the MMSE-CN (p=0.293). The Qmci-CN (AUC 0.91), MoCA-CN (AUC 0.94) and MMSE-CN (AUC 0.79) also had statistically similar accuracy in separating PSD from PSCIND. The MoCA-CN more accurately distinguished between PSCIND and normal cognition than the Qmci-CN (p=0.015). Compared to the MoCA-CN, the administration times of the Qmci-CN (329s vs 611s, respectively, p<0.0001) and MMSE-CN (280 vs 611s, respectively, p<0.0001) were significantly shorter. Conclusion: The Qmci-CN is accurate in identifying PSD and separating PSD from PSCIND in patients post-stroke following rehabilitation and is comparable to the widely-used MoCA-CN, albeit with a significantly shorter administration time. The Qmci-CN had poor accuracy in identifying PSCIND from NC and hence may lack accuracy for certain subgroups. However, given the small sample size, the study is under-powered to show superiority of one instrument over another. Further study is needed to confirm these findings in a larger sample size and in other settings (countries and languages).